2020
DOI: 10.1093/alcalc/agaa103
|View full text |Cite
|
Sign up to set email alerts
|

French Validation of the Alcohol Urge Questionnaire: Psychometric Properties and Relationship with Alcohol Dependence and Drinking Behavior

Abstract: Aim To validate a French translation of the Alcohol Urge Questionnaire (AUQ) that measures craving in patients with alcohol dependence. Method All patients aged > 18 years who were hospitalized for alcohol detoxification from February to May 2019 in the alcohol unit of the Rennes university hospital were eligible. A back-translated version of the AUQ was completed at admission. Patients were interviewed at the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The Alcohol Urge Questionnaire (AUQ) [131–133], its French version [134] and the Questionnaire on Craving for Sweet and Rich Food [135] constitute a third family. They are composed of items evaluated on a 7‐point Likert scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Alcohol Urge Questionnaire (AUQ) [131–133], its French version [134] and the Questionnaire on Craving for Sweet and Rich Food [135] constitute a third family. They are composed of items evaluated on a 7‐point Likert scale.…”
Section: Resultsmentioning
confidence: 99%
“…The Alcohol Urge Questionnaire (AUQ) [131][132][133], its French version [134] and the Questionnaire on Craving for Sweet and Rich studies [131][132][133] conclude that the structure is unidimensional.…”
Section: Conceptual Relationships Between the Instrumentsmentioning
confidence: 99%
“…However, the same scale moderately measured severity of addiction itself, drinking behaviour and mental health. 32 …”
Section: Discussionmentioning
confidence: 99%
“…However, the same scale moderately measured severity of addiction itself, drinking behaviour and mental health. 32 Other studies have found that greater severity of alcohol dependence is associated with greater severity of alcohol craving. 4,33 Of great interest that begs further research into its usefulness in addiction treatment, is our study finding that improvement (reduction in alcohol craving severity, ie, PACS scale scores) occurred to a greater extent among subjects with lower SADD scores (ie, lower severity of alcohol dependence).…”
mentioning
confidence: 96%
“…The Alcohol Urge Questionnaire (AUQ) is an eight-item self-reported questionnaire that assesses drinking urges [ 18 ] and has been validated in French [ 19 ]. Questions are in the form of a 7-point Likert scale, and participants endorse the extent to which they agree or disagree with statements relating to their desire to drink, expectation of a desired outcome from drinking, and inability to avoid drinking if alcohol is available.…”
Section: Methodsmentioning
confidence: 99%